DEVELOPMENT OF MONITORING AND CONTROLLING SYSTEM AT AN AGRICULTURAL ENTERPRISE (Development Service Industry Management, 2024)
This article is dedicated to the issues of building a monitoring and controlling system at an agricultural enterprise. The aim of the study is to analyze, systematize, and generalize existing theoretical and methodological foundations for the implementation of monitoring and controlling in the activities of agricultural enterprises and to build an effective monitoring and controlling system that addresses the current challenges of the economic environment, is adaptive to changing conditions, and ensures comprehensive management of the enterprise at all levels of its operations.The article examines the main aspects of implementing monitoring and controlling systems in agricultural enterprise management, particularly their role in ensuring stable operations and achieving strategic goals. The study presents a detailed analysis of the differences between monitoring and controlling, their interaction, and synergy in the decision-making process. It is found that monitoring performs the function of continuous observation of key enterprise indicators, such as productivity, resource usage, and adherence to established norms. Controlling, unlike monitoring, covers broader functions, including coordination between different functional units, ensuring their synergy in achieving common goals. The article presents the feedback mechanism between monitoring and controlling, which allows for the correction of enterprise activities based on monitoring results and adaptation of the strategy to changes in both the internal and external environments. The study revealed key types of monitoring and controlling systems that are important for agricultural enterprises, including financial, production, strategic, and operational systems. Each of these types has specific tasks that contribute to achieving strategic goals and ensuring the adaptability of the enterprise. Financial controlling focuses on ensuring the financial stability of the enterprise, production controlling on optimizing resources and improving production processes, and strategic controlling on ensuring the alignment of enterprise activities with long-term goalsThe hierarchical structure of the monitoring and controlling system at agricultural enterprises is discussed. It is revealed that effective management at all levels, from strategic to operational, is only possible if data and information from all levels of management activity are integrated. This structure ensures flexibility and operational efficiency, as each level of management, from strategic planning to operational actions, is interconnected and supports the integrity of the system. The study shows that adapting monitoring and controlling systems to the unstable economic environment is critical for ensuring the sustainability of the enterprise.
Keywords: monitoring; controlling; agricultural enterprise; monitoring and controlling system; strategic planning; adaptability